Survey of companion animal veterinarians' antimicrobial drug prescription practices and awareness of antimicrobial drug use guidelines in the United States. (30th January 2022) - Taylor, Daniel D.; Martin, Jennifer N.; Scallan Walter, Elaine J.
Abstract: Antimicrobial drug use in companion animal medicine, the subsequent development of antimicrobial resistance and the potential hazard of animals transmitting resistant bacteria to humans are of increasing concern. Antimicrobial prescription patterns among companion animal veterinarians in the United States are understudied, and the association between antimicrobial drug use guideline awareness and antimicrobial drug prescription practices is unknown. Information on antimicrobial recommendations for five hypothetical clinical scenarios, including canine pyoderma, acute canine diarrhoea, feline lower urinary tract illness, canine dental procedures and feline upper respiratory illness, was gathered using an anonymous, online cross‐sectional survey. A logistic regression approach was used to assess the association between self‐reported awareness of antimicrobial drug use guidelines and prescribing recommendations for the five hypothetical scenarios. Responses ( n = 2, 410) indicated antimicrobial drugs were commonly recommended for the five hypothetical clinical scenarios. After controlling for key demographic characteristics, prescribers who reported an awareness of existing antimicrobial drug use guidelines were significantly less likely to recommend antimicrobial drugs for the scenarios describing feline lower urinary symptoms, feline upper respiratory illness and canine acute diarrhoea. Results from hypothetical clinical scenarios point to the possibility for widespread unsupported prescribing of antimicrobial drugs in companion animal medicine. Additionally, results provide evidence of an association between awareness of antimicrobial drug use guidelines and lower prescribing levels for certain hypothetical disease presentations.